2016
DOI: 10.1016/j.celrep.2016.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 and D2 Receptors Make Dissociable Contributions to Dorsolateral Prefrontal Cortical Regulation of Rule-Guided Oculomotor Behavior

Abstract: Studies of neuromodulation of spatial short-term memory have shown that dopamine D1 receptor (D1R) stimulation in dorsolateral prefrontal cortex (DLPFC) dose-dependently modulates memory activity, whereas D2 receptors (D2Rs) selectively modulate activity related to eye movements hypothesized to encode movement feedback. We examined localized stimulation of D1Rs and D2Rs on DLPFC neurons engaged in a task involving rule representation in memory to guide appropriate eye movements toward or away from a visual sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 50 publications
1
49
1
Order By: Relevance
“…Past studies have reported that drug-induced modulation of discharge characteristics, signal-to-noise ratio, and coding of task attributes can be different between cortical neuronal classes (Mountcastle et al, 1969;Jacob et al, 2013;Ma et al, 2015;Thiele et al, 2016). To ascertain whether cholinergic stimulation had differential effects on putative pyramidal neurons and interneurons defined by electrophysiological characteristics, we performed a similar analysis, whereby we classified prefrontal neurons (n ϭ 68; see Materials and Methods) as broad-spiking (putative pyramidal neurons) or narrow-spiking (putative nonpyramidal neurons; see Materials and Methods;Johnston et al, 2009).…”
Section: Effects Of Carbachol On Putative Pyramidal and Nonpyramidal mentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies have reported that drug-induced modulation of discharge characteristics, signal-to-noise ratio, and coding of task attributes can be different between cortical neuronal classes (Mountcastle et al, 1969;Jacob et al, 2013;Ma et al, 2015;Thiele et al, 2016). To ascertain whether cholinergic stimulation had differential effects on putative pyramidal neurons and interneurons defined by electrophysiological characteristics, we performed a similar analysis, whereby we classified prefrontal neurons (n ϭ 68; see Materials and Methods) as broad-spiking (putative pyramidal neurons) or narrow-spiking (putative nonpyramidal neurons; see Materials and Methods;Johnston et al, 2009).…”
Section: Effects Of Carbachol On Putative Pyramidal and Nonpyramidal mentioning
confidence: 99%
“…However, we cannot discount nicotinic involvement in carbachol's actions reported here. Although nicotinic receptor stimulation can augment working memory activity in PFC (Yang et al, 2013;Sun et al, 2017) and can improve cognitive performance (Terry et al, 2015), other studies have shown that low doses of nicotinic antagonist enhanced attentional performance in rodents (Hahn et al, 2011) and improved delayed match-to-sample performance in monkeys (Terry et al, 1999). In the physiological context, Yang et al (2013) showed that low-dose iontophoretic stimulation of ␣7 nicotinic receptors during oculomotor delayed responses increased macaque DLPFC neuronal excitability and improved memory period spatial tuning, whereas ␣7 receptor antagonist reduced delay period activity and spatial tuning.…”
Section: Effects Of Carbachol On Task Selectivity Of Dlpfc Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and modelling studies of dopamine on persistent activity in working memory have focused on isolated local brain regions, generally in the lateral prefrontal cortex (Brunel and Wang 2001;Durstewitz et al 2000;Jacob et al 2016;Vijayraghavan et al 2016Vijayraghavan et al , 2007Wang et al 2019;Williams and Goldman-Rakic 1995), where it has been shown that dopamine can enhance persistent activity through its effects on the NMDA and GABA receptors (Seamans et al 2001a,b;Seamans and Yang 2004;Wang et al 2013). If the effects of dopamine are truly restricted to small areas of cortex, then dopamine seems unlikely to be able to engage the widespread distributed activity seen during active working memory.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this paradigm as the asynchronous cue (AC) design. This version of the task is often used in primate experiments as well (e.g., Amador et al, 1998;Johnston et al, 2014;Koval et al, 2014;Vijayraghavan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%